Culture on drugs : narco-cultural studies of high modernity - Boothroyd, Dave (Manchester, UK ; New York : Manchester University Press, 2006)
Reconsidering the place of drugs in our culture and the cultural crises they are perceived to endanger, 'Culture on Drugs' argues that the ideas and concepts by which modernity has attained its measure of self-understanding are themselves, in various ways the products of encounters with drugs and their effects.
Deleuze's mathematisation of the series and the function 'LSD'Zabriske Point; From the self as a function of discourse to self-stylisation; Artaud and the artistry of depth; The LSD function and the surface-depth gradient; Deleuze, drugs and the 'folding of thought'; Deleuze and Guattari on the limits, uses and abuses of psychotropic drugs; Foucault, Deleuze and the power of drugs; 8. Cinematic heroin and narcotic modernity; From the heroin scene to the heroin screen; Deleuze and the cinema of heroin; Heroinised bodies; The cinematic fix; Heroin's signature-autograph; Heroin close-up; Heroin as icon; Heroin's redeeming feature (film).
Includes bibliographical references (pages 206-211) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Drugs of abuse -- Social aspects; Narcotics -- Social aspects; Drug abuse -- Psychological aspects; Intellectual life; Social evolution; Cultural Evolution; Drogues -- Aspect social; Toxicomanie -- Aspect psychologique; Vie intellectuelle; Évolution sociale; PSYCHOLOGY -- Psychopathology -- Addiction; SELF-HELP -- Substance Abuse & Addictions -- General; SOCIAL SCIENCE -- Anthropology -- Cultural; Drug abuse -- Psychological aspects; Intellectual life; Social evolution